Wageless Life : a Manifesto for a Future Beyond Capitalism - Shaw, Ian G. R. (Forerunners: Ideas First Ser., 2019)
Drawing up alternate ways to "make a living" beyond capitalism. To live in this world is to be conditioned by capital. Once paired with Western democracy, unfettered capitalism has led to a shrinking economic system that squeezes out billions of people--creating a planet of surplus populations. Wageless Life is a manifesto for building a future beyond the toxic failures of late-stage capitalism. Daring to imagine new social relations, new modes of economic existence, and new collective worlds, the authors provide skills and tools for perceiving--and living in--a post-capitalist future.